PENGEMBANGAN PENGELOLAAN INFAK MELALUI DIGITALISASI PENGELOLAAN DAN PENINGKATAN KEBERAGAMAAN DONATUR DEVELOPMENT OF INFAQ MANAGEMENT THROUGH DIGITALIZATION MANAGEMENT AND IMPROVEMENT OF DONOR'S DIVERSITY - Hendi Suhendi; Muhammad Fauzi Arif (UPT Publikasi Ilmiah (Universitas Islam Bandung), 2021)
The realization of Baitul Maal Unisba's infaq receipts that are not in line with the existing donation potential, causes the level of financing ability of the scholarship program run by Baitul Maal Unisba has not been fulfilled optimally. For this reason, this research was conducted with the aim of knowing the infaq management carried out by Baitul Maal Unisba, and knowing the strategy for increasing infaq through digitalization of management systems and services. This research is a case study research using descriptive and participatory analysis methods, namely methods that try to solve problems based on the data analyzed and interpreted. The data obtained shows that the infaq collection process has not been optimally carried out by Baitul Maal Unisba, one of which is shown by the absence of a digital- based management information system or application. The results of the study reveal that in order to achieve an increase in collection according to the expected target, the manager must take the following steps: increasing the capacity and competence of human resources, preparing digital technology-based facilities and infrastructure, creating creative and innovative programs, carrying out da'wah activities in order to increase understanding and concern donors, digitizing management information systems, digitizing donation services and digitizing collections through outreach and promotion activities. Realisasi penerimaan infak Baitul Maal Unisba yang belum selaras dengan potensi donasi yang ada, menyebabkan tingkat kemampuan pembiayaan program beasiswa yang dijalankan Baitul Maal Unisba belum terpenuhi dengan optimal. Untuk itu penelitian ini dilakukan dengan tujuan mengetahui pengelolaan infak yang dilakukan Baitul Maal Unisba, serta mengetahui strategi peningkatan infak melalui digitalisasi sistem pengelolaan dan layanan. Penelitian ini merupakan penelitian studi kasus dengan menggunakan metode analisis deskriptif dan partisipatory, yaitu metode yang berusaha memecahkan masalah berdasarkan data-data yang dianalisis dan diinterpretasikan. Datayang diperoleh menunjukan bahwa belum optimalnya proses penghimpunan infak yang dilakukan oleh Baitul Maal Unisba, salah satunya ditunjukan dengan belum adanya sistem informasi manajemen berbasis digital atau aplikasi. Hasil penelitian mengungkapkan agar tercapai peningkatan penghimpunan sesuai target yang diharapkan maka pengelola harus melakukan langkah-langkah sebagai berikut : peningkatan kapasitas dan kompetensi SDM, menyiapkan sarana dan prasana berbasis teknologi digital, menciptakan program kreatif dan inovatif, menjalankan aktivitas dakwah dalam rangka peningkatan pemahaman dan kepedulian donatur, digitalisasi sistem informasi manajemen pengelolaan, digitalisasi layanan kemudahan donasi serta digitalisasi penghimpunan melalui aktivitas sosialisasi dan promosi.